2013
DOI: 10.4269/ajtmh.12-0629
|View full text |Cite
|
Sign up to set email alerts
|

Household Environmental Conditions Are Associated with Enteropathy and Impaired Growth in Rural Bangladesh

Abstract: We assessed the relationship of fecal environmental contamination and environmental enteropathy. We compared markers of environmental enteropathy, parasite burden, and growth in 119 Bangladeshi children (≤ 48 months of age) across rural Bangladesh living in different levels of household environmental cleanliness defined by objective indicators of water quality and sanitary and hand-washing infrastructure. Adjusted for potential confounding characteristics, children from clean households had 0.54 SDs (95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
280
4
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 293 publications
(309 citation statements)
references
References 32 publications
20
280
4
5
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Although its etiology is not fully defined, EE is thought to be caused by unsanitary environmental conditions leading to repeated exposures to enteric pathogens. 11 The gold standard to measure EE is endoscopy and biopsy, which is impractical in most low-income settings. 12 Therefore, generally markers of intestinal barrier function and absorptive capacity of the small intestine are used as surrogate measures.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Although its etiology is not fully defined, EE is thought to be caused by unsanitary environmental conditions leading to repeated exposures to enteric pathogens. 11 The gold standard to measure EE is endoscopy and biopsy, which is impractical in most low-income settings. 12 Therefore, generally markers of intestinal barrier function and absorptive capacity of the small intestine are used as surrogate measures.…”
Section: Introductionmentioning
confidence: 99%
“…Humphrey (2009) posited that chronic but subclinical "environmental enteropathy," caused by ingestion of fecal pathogens, may also lead to slowed growth. Lin et al (2013) found associations among fecal environmental contamination, enteropathy, and child height in Bangladesh. Poor sanitation can also spread parasitic infections, which are rarely fatal by themselves but contribute to poor health and poor physical growth (Haque 2007).…”
Section: Background: Population Density Sanitation and Disease Extementioning
confidence: 99%
“…Evidence is converging that this chronic 4 disorder of the small intestine, due to "faecal bacteria ingested in large quantities by young children living in conditions of poor sanitation and hygiene" (Humphrey, 2009(Humphrey, , 1032, could cause widespread malabsorption of nutrients among children living in places where open defecation is common (Petri et al, 2008;Mondal et al, 2011;Korpe and Petri, 2012). In a recent study in rural Bangladesh, Lin et al (2013) show that children exposed to less sanitary conditions show more biologically measured markers of enteropathy and do not grow as tall (also see Kosek et al, 2013). These epidemiological and medical studies, combined with a growing literature within economics that documents effects of poor sanitation on earlylife health, 2 suggest that diminished human capital and cognitive skills may be a further consequence of open defecation.…”
Section: Early Life Health and Cognitive Skillsmentioning
confidence: 99%